Antibacterial nanocomposite with gradient distribution of particle size

CN122974299APending Publication Date: 2026-10-27DAYAO BIOMEDICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611110794.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-27

Smart Images

  • Figure CN122974299A_ABST
    Figure CN122974299A_ABST
Patent Text Reader

Abstract

The present application relates to the technical fields of nanocomposite and antibacterial technology, and discloses an antibacterial nanocomposite with gradient distribution of particle size. The nanocomposite comprises: a photocatalytic material for loading antibacterial metal nanoparticles and generating photocatalytic antibacterial activity; an interface bonding layer covering the surface of the photocatalytic material; and antibacterial metal nanoparticles fixed on the surface of the photocatalytic material in a point-like loading mode through the interface bonding layer. The antibacterial metal nanoparticles comprise first antibacterial metal nanoparticles and second antibacterial metal nanoparticles, the first antibacterial metal nanoparticles are directly attached to the surface of the interface bonding layer, and at least a part of the second antibacterial metal nanoparticles are attached to the surface of the first antibacterial metal nanoparticles, forming a stacked gradient structure with increasing particle size from inside to outside. The present application realizes rapid sterilization in the early stage and long-term antibacterial effect in the later stage through a polydopamine interface bonding layer and a two-step photodeposition method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanocomposite materials and antibacterial technology, specifically relating to an antibacterial nanocomposite material with a particle size gradient distribution. Background Technology

[0002] Microbial contamination of surfaces in food processing, medical devices, and daily consumer products is becoming increasingly prominent, making the development of efficient, long-lasting, and safe antibacterial materials a research hotspot. Existing antibacterial technologies mainly fall into two categories: first, photocatalytic materials (such as titanium dioxide and zinc oxide), which generate reactive oxygen species (ROS) to kill bacteria under light conditions, but their antibacterial effect significantly decreases in the absence of light or in weak light environments; second, nano-silver materials, which rely on the release of silver ions to inhibit bacteria, but suffer from problems such as excessively rapid initial release, insufficient later release, and easy aggregation and inactivation of nano-silver.

[0003] To address the aforementioned shortcomings, researchers have attempted to combine photocatalytic materials with silver nanoparticles to achieve a dual antibacterial mechanism of photoresponse and silver ion release. However, existing composite structures mostly employ physical mixing or simple loading methods, which present the following technical problems: (1) The distribution of silver nanoparticles on the surface of photocatalytic materials is uneven, and they are prone to agglomeration, resulting in a wide particle size distribution and a high PDI value, which affects the antibacterial stability; (2) There is a lack of strong interfacial bonding between silver nanoparticles and photocatalytic materials, and silver nanoparticles are prone to detachment during use, resulting in poor antibacterial durability; (3) It is impossible to simultaneously meet the dual requirements of "initial rapid sterilization" and "long-term sustained-release antibacterial", and single-size silver nanoparticles are difficult to balance the release rate and release duration.

[0004] Therefore, there is an urgent need to provide an antibacterial nanocomposite material with stable silver nanoparticle loading, controllable particle size, and gradient release characteristics. Summary of the Invention

[0005] The purpose of this invention is to provide an antibacterial nanocomposite material with a particle size gradient distribution to solve the problems of uneven distribution of antibacterial metal nanoparticles, weak interfacial bonding, and difficulty in achieving both initial rapid sterilization and long-term sustained-release antibacterial effect in photocatalysis-silver nanocomposite structures.

[0006] Based on the above concept, the technical solution adopted by this invention is as follows: According to a first aspect of the present invention, an antibacterial nanocomposite material with a particle size gradient distribution is provided, comprising a photocatalytic material for loading antibacterial metal nanoparticles and generating photocatalytic antibacterial activity; An interface bonding layer is used to cover the surface of the photocatalytic material and connect antibacterial metal nanoparticles; And antibacterial metal nanoparticles, which are fixed on the surface of the photocatalytic material in a dotted loading manner through the interface bonding layer; The antibacterial metal nanoparticles include a first antibacterial metal nanoparticle and a second antibacterial metal nanoparticle. The first antibacterial metal nanoparticle is directly attached to the surface of the interface bonding layer. At least a portion of the second antibacterial metal nanoparticle is attached to the surface of the first antibacterial metal nanoparticle.

[0007] In some embodiments, the particle size D50 of the first antibacterial metal nanoparticle is 1-3 nm, the particle size D50 of the second antibacterial metal nanoparticle is 5-10 nm, and the overall particle size D50 of the antibacterial metal nanoparticle is 1-10 nm, with a particle size distribution coefficient PDI ≤ 0.3.

[0008] In some embodiments, the ratio of the first antibacterial metal nanoparticles to the second antibacterial metal nanoparticles is 1:0.5 to 1:3.

[0009] Furthermore, the percentage of the coverage area of ​​the first antibacterial metal nanoparticles on the surface of the interface bonding layer is 10%-30%; at least a portion of the second antibacterial metal nanoparticles covers the surface of the first antibacterial metal nanoparticles.

[0010] Optionally, the photocatalytic material is selected from titanium dioxide or zinc oxide, with a particle size of 100-500 nm.

[0011] Optionally, the antibacterial metal nanoparticles include any one or more of silver, gold, platinum, palladium, copper, or zinc.

[0012] According to a second aspect of the present invention, an antibacterial nanocomposite material with a particle size gradient distribution is provided, comprising the following steps: S1. Disperse the photocatalytic material in a dopamine solution and stir for 12-24 hours to form a polydopamine interface bonding layer on the outer surface of the photocatalytic material; S2. After separating and washing the product obtained in step S1, disperse it in a first aqueous solution with a concentration of 0.1-1 mM, and expose it to light with an intensity of 0.1-1 mW / cm². 2 Under ultraviolet light irradiation, the first antibacterial metal nanoparticles are deposited on the surface of the polydopamine interface layer for 5-15 minutes. S3. After separating and washing the product obtained in step S2, disperse it in a second aqueous solution with a concentration of 1-5 mM, and expose it to light with an intensity of 10-50 mW / cm². 2 Under ultraviolet light irradiation, after 30-60 minutes of deposition, a second antibacterial metal nanoparticle is formed on the surface of the polydopamine interface bonding layer.

[0013] In some embodiments, the concentration of the dopamine solution is 1-5 mg / mL, the pH is adjusted to 8.0-9.0, and the reaction temperature is 20-40°C.

[0014] In some embodiments, the first aqueous solution and the second aqueous solution further contain a hole sacrificial agent selected from methanol, ethanol, isopropanol or triethanolamine.

[0015] The beneficial effects of this invention are as follows: 1. This invention uses a polydopamine interfacial bonding layer to firmly anchor antibacterial metal nanoparticles onto the surface of a photocatalytic material in a point-like loading manner, forming a stacked gradient structure of first and second antibacterial metal nanoparticles, wherein the second antibacterial metal nanoparticles are attached to the surface of the first antibacterial metal nanoparticles. This stacked structure allows the outer layer of large-particle antibacterial metal nanoparticles to be directly exposed to the environment, rapidly releasing silver ions in the initial stage for immediate sterilization; the inner layer of small-particle antibacterial metal nanoparticles is partially covered by the outer large-particles, restricting their release path, and continuously and slowly releasing ions in the later stage to achieve long-term antibacterial effect. At the same time, combined with the photo-induced reactive oxygen species generation of the photocatalytic material, the synergistic antibacterial efficiency of the composite material is improved.

[0016] 2. This invention employs a two-step photodeposition method. By controlling the ratio of low to high light intensity, as well as ion concentration and deposition time, the stacking gradient structure of antibacterial metal nanoparticles can be modulated without adding additional reducing agents. The polydopamine interfacial bonding layer not only enhances the anchoring strength of the silver nanoparticles but also provides abundant nucleation sites, ensuring the uniform dispersion and stable stacking of the antibacterial metal nanoparticles. The resulting composite material exhibits high structural stability and can be widely applied in wound dressings, medical device coatings, antibacterial sprays, and water treatment. Attached Figure Description

[0017] Figure 1 This is a flowchart of the preparation method of the present invention. Detailed Implementation

[0018] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples of apparatuses and methods consistent with some aspects of the invention as detailed in the appended claims.

[0019] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. Unless otherwise defined, the technical or scientific terms used in this application should be understood in their ordinary sense by one of ordinary skill in the art to which this invention pertains. The words “a” or “one” and similar terms used in this application specification and claims do not indicate a limitation of quantity, but rather indicate the presence of at least one. “A plurality” means two or more. The words “comprising” or “including” and similar terms mean that the element or object preceding “comprising” or “including” covers the element or object listed following “comprising” or “including” and its equivalents, and does not exclude other elements or objects. The words “connected” or “linked” and similar terms are not limited to physical or mechanical connections and can include electrical connections, whether direct or indirect. The words “above” and / or “below” and similar terms are for ease of description only and are not limited to a location or spatial orientation. The singular forms “a,” “the,” and “the” used in this application specification and appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0020] The technical concept of this invention includes: Existing photocatalytic-antibacterial metal nanoparticle composite antibacterial materials suffer from the contradiction of uneven distribution of antibacterial metal nanoparticles, weak interfacial bonding, and difficulty in achieving both immediate sterilization and long-term antibacterial effect. Specifically, antibacterial metal nanoparticles of a single particle size cannot simultaneously meet the requirements of rapid release and sustained release; physical mixing or simple loading methods lead to easy aggregation and detachment of antibacterial metal nanoparticles, covering photocatalytic active sites and limiting synergistic antibacterial effects. In addition, existing preparation methods make it difficult to precisely control the particle size and spatial arrangement of antibacterial metal nanoparticles, resulting in poor batch stability of composite materials and failing to meet the requirements of practical applications.

[0021] To address the aforementioned issues, this invention proposes pre-forming a polydopamine interfacial bonding layer on the surface of a photocatalytic material. This layer utilizes its abundant functional groups to anchor antibacterial metal nanoparticles. Small and large-diameter antibacterial metal nanoparticles are then sequentially deposited using a two-step photodeposition method, with the large-diameter particles adhering to the surface of the small-diameter particles, forming a stacked gradient structure with increasing particle size from the inside out. This structure offers the following advantages: the polydopamine layer provides strong interfacial bonding, preventing the antibacterial metal nanoparticles from detaching; the small-diameter antibacterial metal nanoparticles are located at the bottom layer and partially covered by the outer large-diameter particles, thus spatially blocking the release pathway of their active metal ions (such as silver and copper ions) and exhibiting slow-release characteristics; the outer large-diameter antibacterial metal nanoparticles are directly exposed, allowing for rapid release of active metal ions for immediate sterilization. Simultaneously, the point-like loading method retains most of the active sites on the surface of the photocatalytic material, enabling it to efficiently generate reactive oxygen species under illumination, forming a spatiotemporally synergistic antibacterial network with the release of active metal ions.

[0022] Therefore, this invention solves the technical problems of easy aggregation of antibacterial metal nanoparticles, uncontrollable release rate, and shielded photocatalytic activity in traditional composite materials by synergistic design of interface bonding layer and particle size gradient stacking structure, and achieves the unity of instant sterilization and long-term antibacterial effect, providing a feasible technical path for high-performance antibacterial nanocomposites.

[0023] This application provides an antibacterial nanocomposite material with a particle size gradient distribution, including a photocatalytic material, for loading antibacterial metal nanoparticles and generating photocatalytic antibacterial activity; An interface bonding layer is used to cover the surface of the photocatalytic material and connect antibacterial metal nanoparticles; And antibacterial metal nanoparticles, which are fixed on the surface of the photocatalytic material in a dotted loading manner through the interface bonding layer; The antibacterial metal nanoparticles include a first antibacterial metal nanoparticle and a second antibacterial metal nanoparticle. The first antibacterial metal nanoparticle is directly attached to the surface of the interface bonding layer. At least a portion of the second antibacterial metal nanoparticle is attached to the surface of the first antibacterial metal nanoparticle.

[0024] This invention uses a polydopamine interfacial bonding layer to firmly anchor antibacterial metal nanoparticles onto the surface of a photocatalytic material in a point-like loading manner, forming a stacked gradient structure of first and second antibacterial metal nanoparticles, wherein the second antibacterial metal nanoparticles are attached to the surface of the first antibacterial metal nanoparticles. This stacked structure allows the outer layer of large-particle antibacterial metal nanoparticles to be directly exposed to the environment, rapidly releasing silver ions in the initial stage for immediate sterilization; the inner layer of small-particle antibacterial metal nanoparticles is partially covered by the outer large-particles, restricting their release path, and continuously and slowly releasing silver ions in the later stage for long-term antibacterial effect. At the same time, combined with the photo-induced reactive oxygen species generation of the photocatalytic material, the synergistic antibacterial efficiency of the composite material is improved. This invention uses a two-step photodeposition method, and by controlling the ratio of low to high light intensity, as well as the concentration of antibacterial metal nanoparticles and deposition time, the stacked gradient structure of antibacterial metal nanoparticles can be precisely controlled without adding additional reducing agents. The polydopamine interfacial bonding layer not only enhances the anchoring strength of antibacterial metal nanoparticles, but also provides abundant nucleation sites, ensuring the uniform dispersion and stable stacking of antibacterial metal nanoparticles. The resulting composite material has high structural stability and can be widely used in wound dressings, medical device coatings, antibacterial sprays, and water treatment.

[0025] The following describes in detail an antibacterial nanocomposite material with a particle size gradient distribution provided in this application, with reference to embodiments and comparative examples.

[0026] Example 1 The antibacterial nanocomposite material with a gradient particle size distribution described in this embodiment is composed of a photocatalytic material, an interfacial bonding layer, and silver nanoparticles. The photocatalytic material is titanium dioxide particles with a particle size of 300 nm; the interfacial bonding layer is a polydopamine layer with a thickness of 2.5 nm; the silver nanoparticles include first silver nanoparticles and second silver nanoparticles. The first silver nanoparticles are directly attached to the surface of the polydopamine layer, and the second silver nanoparticles are attached to the surface of the first silver nanoparticles. The particle size D50 of the first silver nanoparticles is 2-3 nm, and the particle size D50 of the second silver nanoparticles is 7-9 nm. The ratio of the number of first silver nanoparticles to the number of second silver nanoparticles is 1:1.5.

[0027] The preparation method of the antibacterial nanocomposite material includes the following steps: Step S1: 1.0 g of titanium dioxide particles (300 nm in diameter) were dispersed in 1.0 L of dopamine aqueous solution with a concentration of 3 mg / mL. The pH was adjusted to 8.5 with ammonia, and the mixture was stirred at 30 °C for 18 hours. After the reaction, the mixture was centrifuged, washed three times with deionized water, and vacuum dried at 50 °C for 6 hours to obtain titanium dioxide material with a polydopamine interfacial layer. The thickness of the polydopamine interfacial layer was measured to be 2.5 nm by transmission electron microscopy (TEM).

[0028] Step S2: Disperse all the product obtained in step S1 in 1.0 L of a first aqueous solution of silver nitrate with a concentration of 0.5 mM, and add 0.5 vol% ethanol as a hole sacrificial agent. Perform photodeposition under ultraviolet light irradiation at an intensity of 0.5 mW / cm². 2 The deposition time was 10 minutes, with stirring at 300 rpm. After deposition, the mixture was centrifuged and washed three times with deionized water to obtain an intermediate product loaded with the first silver nanoparticle. High-resolution transmission electron microscopy showed that the particle size D50 of the first silver nanoparticle was 2-3 nm, and the coverage percentage on the polydopamine layer surface was approximately 20%.

[0029] Step S3: The product from step S2 is dispersed in 1.0 L of a second aqueous solution of silver nitrate with a concentration of 3 mM, and 0.5 vol% ethanol is added as a hole sacrificial agent. Photodeposition is performed under ultraviolet light irradiation at an intensity of 30 mW / cm². 2 The deposition time was 45 minutes, with stirring at 300 rpm. After deposition, the mixture was centrifuged, washed three times with deionized water, and vacuum dried at 60°C for 12 hours to obtain the final antibacterial nanocomposite material.

[0030] Example 2 Everything else is the same as in Example 1, except that: In step S1, the concentration of the dopamine aqueous solution is 1 mg / mL, the pH is adjusted to 8.5, and the reaction is carried out at 30°C with stirring for 18 hours, resulting in a polydopamine interfacial bonding layer with a thickness of 0.8 nm. In step S2, the particle size D50 of the first silver nanoparticles is 1-2 nm, and the coverage percentage is approximately 10%. In step S3, the particle size D50 of the second silver nanoparticles is 5-7 nm. In the resulting antibacterial nanocomposite material, the ratio of the first silver nanoparticles to the second silver nanoparticles is approximately 1:0.8. The overall particle size D50 of the silver nanoparticles is 1-7 nm, and the particle size distribution index (PDI) is 0.22.

[0031] Example 3 Everything else is the same as in Example 1, except that: In step S1, the concentration of the dopamine aqueous solution is 5 mg / mL, the pH is adjusted to 8.5, and the reaction is carried out at 30°C with stirring for 18 hours, resulting in a polydopamine interfacial bonding layer with a thickness of 4.8 nm. In step S2, the first silver nanoparticle has a particle size D50 of 2-3 nm and a coverage percentage of approximately 28%. In step S3, the second silver nanoparticle has a particle size D50 of 8-10 nm. In the resulting antibacterial nanocomposite material, the ratio of the first silver nanoparticle to the second silver nanoparticle is approximately 1:2.5. The overall particle size D50 of the silver nanoparticles is 2-10 nm, and the particle size distribution index (PDI) is 0.28.

[0032] Example 4 Everything else is the same as in Example 1, except that: In step S2, the concentration of the first aqueous solution of silver nitrate is 0.1 mM, the deposition time remains 10 minutes, and the light intensity remains 0.5 mW / cm². 2 The resulting first silver nanoparticles had a particle size D50 of 1-2 nm and a coverage percentage of approximately 8%. Step S3 was the same as in Example 1 (3 mM AgNO3, 30 mW / cm³). 2 The first silver nanoparticles were subjected to a 45-minute incubation period (45 min). The particle size D50 of the second silver nanoparticle was 7-9 nm. In the obtained antibacterial nanocomposite material, the ratio of the number of first silver nanoparticles to the number of second silver nanoparticles was approximately 1:1.8. The overall particle size D50 of the silver nanoparticles was measured to be 1-9 nm, and the particle size distribution index (PDI) was 0.24.

[0033] Example 5 Everything else is the same as in Example 1, except that: In step S3, the concentration of the second aqueous solution of silver nitrate is 5 mM, and the light intensity remains 30 mW / cm². 2 The deposition time remained at 45 minutes. The resulting second silver nanoparticles had a particle size D50 of 9-12 nm. The first silver nanoparticles were the same as in Example 1 (particle size 2-3 nm). In the resulting antibacterial nanocomposite material, the ratio of the first to the second silver nanoparticles was approximately 1:1.2. Testing showed that the overall particle size D50 of the silver nanoparticles was 2-12 nm, and the particle size distribution index (PDI) was 0.31.

[0034] Example 6 Everything else is the same as in Example 1, except that: In step S2, the first aqueous solution of silver nitrate was replaced with a first aqueous solution of copper nitrate at a concentration of 0.5 mM, and 0.5 vol% ethanol was added as a hole sacrificial agent. Photodeposition was performed under ultraviolet light irradiation at an intensity of 0.5 mW / cm² for 20 minutes, with stirring at 300 rpm. After deposition, the mixture was centrifuged and washed three times with deionized water to obtain the intermediate product loaded with the first copper nanoparticles.

[0035] In step S3, the second aqueous solution of silver nitrate was replaced with a second aqueous solution of copper nitrate at a concentration of 3 mM, and 0.5 vol% ethanol was added as a hole sacrificial agent. Photodeposition was performed under ultraviolet light irradiation at an intensity of 30 mW / cm² for 90 minutes, with stirring at 300 rpm. After deposition, the mixture was centrifuged, washed three times with deionized water, and vacuum-dried at 60°C for 12 hours to obtain the final antibacterial nanocomposite material.

[0036] Comparative Example 1 (without polydopamine interface layer) Everything else is the same as in Example 1, except that: Step S1 was omitted, meaning the dopamine treatment of the titanium dioxide particles was not performed; instead, the titanium dioxide particles were directly photodeposited in steps S2 and S3. In the resulting composite material, the silver nanoparticles were severely agglomerated, unable to form dot-like loading. TEM observation revealed an extremely wide particle size distribution (2-25 nm) for the silver nanoparticles, with a PDI of 0.58, and most of the silver nanoparticles detached during washing. The photocatalytic antibacterial activity significantly decreased, with the antibacterial rate dropping below 60% after just one cycle.

[0037] Comparative Example 2 (S2 light intensity is too high) Everything else is the same as in Example 1, except that: In step S2, the ultraviolet light intensity is 5 mW / cm². 2 Under the same conditions, the first silver nanoparticles had a particle size D50 of 4-6 nm and a coverage percentage of approximately 35%. After step S3, the first silver nanoparticles overlapped with the subsequently deposited second silver nanoparticles, failing to form a significant particle size gradient. The silver ion release curve showed no two-phase characteristics, and the initial release rate was low (only 0.3 μg·mg). -1 ·h -1 The cumulative release over 24 hours is insufficient.

[0038] Comparative Example 3 (S3 light intensity is too low) Everything else is the same as in Example 1, except that: In step S1, the ultraviolet light intensity is 5 mW / cm². 2Under otherwise unchanged conditions, the resulting second silver nanoparticles had a particle size D50 of only 3-5 nm, almost overlapping with the first silver nanoparticles, and could not form large-size particles. The composite material exhibited an excessively rapid silver ion release rate (>0.5 μg·mg) in the later stages. -1 ·h -1 It cannot achieve long-lasting antibacterial effect, and its antibacterial activity decreases significantly after 24 hours.

[0039] Comparative Example 4 (deposition order reversed) Everything else is the same as in Example 1, except that: First, high-intensity deposition in step S3 is performed, followed by low-intensity deposition in step S2. In the resulting composite material, the large-particle-size silver nanoparticles deposited first adhere directly to the surface of the polydopamine layer, while the small-particle-size silver nanoparticles deposited later adhere to the surface of the large-particle-size silver nanoparticles or fill the gaps. This structure results in the outer small-particle-size silver nanoparticles releasing silver ions explosively in the initial stage (release rate >2.5 μg·mg in the first 2 hours). -1 ·h -1 Increased cytotoxicity; hindered release of large-particle-size silver nanoparticles in the inner layer, resulting in insufficient antibacterial ability in the later stages.

[0040] Comparative Example 5 (Light Intensity Ratio Too Low) Everything else is the same as in Example 1, except that: The light intensity in step S2 is 0.8 mW / cm², and the light intensity in step S3 is 2 mW / cm². 2 With all other conditions unchanged, the resulting first silver nanoparticles had a D50 of 2-4 nm, and the second silver nanoparticles had a D50 of 3-6 nm. The particle size ranges of the two nanoparticles overlapped significantly, making it impossible to form a clear stacked gradient structure. The silver ion release curves were between those of Example 1 and Comparative Example 2, showing no biphasic characteristics.

[0041] Table 1 Comparison of experimental results between the examples and the comparative examples

[0042] As shown in Table 1, regarding the silver ion release behavior, Examples 1-5 all exhibited typical biphasic release characteristics: the initial release rate was 0.9-1.6 μg·mg in the first 0-2 hours. -1 ·h -1 The release rate in the later stage (2-24 hours) was 0.08-0.18 μg·mg. -1 ·h -1Furthermore, the initial release accounts for 40-60% of the total release. This "fast at first, slow later" release curve originates from the stacked gradient structure of this invention—the outer layer of large-diameter silver nanoparticles is directly exposed to the environment, rapidly releasing silver ions in the initial stage to achieve immediate sterilization; the inner layer of small-diameter silver nanoparticles is partially covered by the outer layer of large particles, obstructing the release path, resulting in a slow and sustained release in the later stage. In Comparative Example 2, due to the excessively large particle size (4-6 nm) and excessively high coverage area (35%) of the first silver nanoparticles, the initial release rate was only 0.3 μg·mg. -1 ·h -1 The initial bactericidal ability was insufficient; in Comparative Example 3, due to the excessively small size of the second silver nanoparticles (3-5 nm), the release rate in the later stage reached as high as 0.52 μg·mg. -1 ·h -1 It cannot achieve long-term antibacterial effect and poses a risk of silver ion toxicity; in Comparative Example 4, when the deposition order was reversed, the outer layer small particles caused an initial explosive release (2.6 μg·mg). -1 ·h -1 The release of large particles in the inner layer is hindered, but the release rate in the later stages is still as high as 0.35 μg·mg. -1 ·h -1 In Comparative Example 5, the release behavior was out of control; due to the excessively low light intensity ratio, the particle sizes of the two-step deposition overlapped, and the two-phase characteristics disappeared. The above comparisons fully demonstrate that only by following the deposition sequence and light intensity ratio specified in this invention can an ideal "fast then slow" two-phase release curve be obtained.

[0043] The antibacterial performance test results showed that Examples 1-5 achieved a synergistic antibacterial rate of over 99.2% against Escherichia coli and Staphylococcus aureus under simulated sunlight irradiation (light + no light synergistic conditions) for 2 hours, with Example 1 reaching as high as 99.8%. In contrast, the antibacterial rate of Comparative Example 1 was only 78.5%, and the antibacterial rates of Comparative Examples 2-5 ranged from 82.1% to 88.2%, all significantly lower than those of Examples 1-5. This is because the biphasic silver ion release provided by the particle size gradient structure in this invention and the reactive oxygen species generated by the photocatalytic material form a spatiotemporal synergistic antibacterial network: initially, silver ions rapidly kill surface bacteria, and later, silver ions continuously inhibit bacterial regeneration, while the reactive oxygen species generated under light further damage the cell membranes of residual bacteria. Comparative Example 1 showed the worst antibacterial effect due to the uncontrollable release of silver ions caused by the aggregation and detachment of silver nanoparticles and the covering of photocatalytic active sites. Comparative Example 2 showed insufficient release of silver ions in the early stage, Comparative Example 3 showed excessive release in the later stage leading to rapid depletion of silver ions, Comparative Example 4 showed explosive release in the early stage and uncontrolled release in the later stage, and Comparative Example 5 showed a flat release curve. None of these results in the formation of efficient synergistic antibacterial effects.

[0044] Furthermore, in Example 6, nano-copper was used instead of nano-silver, and its metal ion release also exhibited a biphasic characteristic (initial 1.0 μg·mg). -1 ·h -1 Later, 0.15 μg·mg-1 ·h -1 The synergistic antibacterial rate reached 98.70%, and the activity retention rate after 5 cycles was 94.20%, indicating that the particle size gradient stacking structure of the present invention is also applicable to the nano-copper system and has good universality.

[0045] Regarding cycle stability, the activity retention rates of Examples 1-5 after 5 cycles were all above 93.1%, with Example 3 reaching 97.2%; while the activity retention rate of Comparative Example 1 was only 42.3%, and that of Comparative Examples 2-5 was 55.6%-72.5%. Meanwhile, the nano-silver interface detachment rates of Examples 1-5 were all below 1.8%, while that of Comparative Example 1 was as high as 18.5%, and the other comparative examples also exceeded 4.8%. This is attributed to the strong chemical anchoring effect of the polydopamine interface bonding layer: the catechol groups in polydopamine can form coordination bonds with silver ions, firmly fixing the reduced nano-silver to the surface of the photocatalytic material. Even after multiple washings and cycles, the nano-silver is not easily detached. Comparative Example 1 omitted the polydopamine layer, and the nano-silver relied solely on physical adsorption loading, making it extremely prone to aggregation and detachment; although Comparative Examples 2-5 had dopamine layers, due to uncontrolled particle size gradients or improper deposition conditions, some nano-silver did not bond firmly to the interface, resulting in detachment rates still above 4.8%. The above results demonstrate that the presence of the polydopamine interfacial bonding layer and the controllable stacking gradient structure are essential technical features for ensuring the long-term stability of the composite material.

[0046] Furthermore, the antibacterial nanocomposite material provided by this invention also exhibits excellent antiviral properties. Examples 1-5, under simulated sunlight irradiation, all achieved an inactivation rate of over 99.4% against human immunodeficiency virus (HIV) within 2 hours, with Example 1 reaching as high as 99.9%. This is attributed to the synergistic antiviral network formed by the efficient silver ion release resulting from the particle size gradient structure and the reactive oxygen species (ROS) generated by the photocatalytic material: this stacked structure achieves high-concentration, rapid ion release in the initial stage through the high specific surface area of ​​the inner small-diameter particles and partially exposed surfaces, thus achieving immediate sterilization; simultaneously, the stacked coverage of the outer large-diameter particles forms a physical diffusion barrier layer, effectively extending the release path of ions from the inner small-diameter particles, allowing ions to continuously and slowly seep out in the later stages, thereby achieving long-lasting antibacterial effects. Simultaneously, the ROS generated by the photocatalytic material under light irradiation can effectively attack the HIV RNA genome, causing it to break down and degrade, thereby achieving synergistic inactivation through multiple targets and pathways. In contrast, Comparative Example 1 showed a virus inactivation rate of only 65.3% due to the aggregation and detachment of silver nanoparticles, preventing the synergistic effect of silver ions and ROS. Comparative Examples 2-5 also exhibited significantly lower antiviral effects than the examples due to the lack or uncontrolled biphasic release characteristics. It should be noted that the antibacterial nanocomposite material provided by this invention has passed HIV antiviral activity certification, further confirming its reliability and broad-spectrum effectiveness in extreme virus elimination scenarios. The above results demonstrate that the stacked gradient structure of this invention is not only highly effective in the antibacterial field but also shows broad promise in the inactivation of highly pathogenic viruses such as HIV.

[0047] In summary, the data from Examples 1-5 consistently demonstrate that the stacked gradient structure constructed by the present invention using a polydopamine interface bonding layer and a two-step photodeposition method (low light intensity followed by high light intensity, with a light intensity ratio ≥ 10 times) can achieve uniform dispersion, firm anchoring, biphasic controllable release, and highly efficient synergistic antibacterial properties of silver nanoparticles. Comparative Examples 1-5, however, verified that omitting the interface layer, deviating from the light intensity range, reversing the deposition order, and reducing the light intensity ratio all lead to a significant decrease in one or more performance characteristics. Therefore, the technical features and parameter ranges defined in this invention possess clear non-obviousness and substantial technical advancement. It should be understood that this invention is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. Therefore, this invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the claims of this patent.

Claims

1. An antibacterial nanocomposite material with a particle size gradient distribution, characterized in that, include Photocatalytic materials are used to load antibacterial metal nanoparticles and generate photocatalytic antibacterial activity. An interface bonding layer is used to cover the surface of the photocatalytic material and to connect antibacterial metal nanoparticles; And antibacterial metal nanoparticles, which are fixed on the surface of the photocatalytic material in a dotted loading manner through the interface bonding layer; The antibacterial metal nanoparticles include a first antibacterial metal nanoparticle and a second antibacterial metal nanoparticle. The first antibacterial metal nanoparticle is directly attached to the surface of the interface bonding layer. At least a portion of the second antibacterial metal nanoparticle is attached to the surface of the first antibacterial metal nanoparticle.

2. The antibacterial nanocomposite material with a particle size gradient distribution according to claim 1, characterized in that, The first antibacterial metal nanoparticle has a particle size D50 of 1-3 nm, the second antibacterial metal nanoparticle has a particle size D50 of 5-10 nm, and the overall particle size D50 of the antibacterial metal nanoparticle is 1-10 nm, with a particle size distribution coefficient PDI ≤ 0.

3.

3. The antibacterial nanocomposite material with a particle size gradient distribution according to claim 1, characterized in that, The ratio of the first antibacterial metal nanoparticle to the second antibacterial metal nanoparticle is 1:0.5 to 1:

3.

4. The antibacterial nanocomposite material with a particle size gradient distribution according to claim 1, characterized in that, The first antibacterial metal nanoparticles cover 10%-30% of the surface area of ​​the interface bonding layer; at least a portion of the second antibacterial metal nanoparticles covers the surface of the first antibacterial metal nanoparticles.

5. The antibacterial nanocomposite material with a particle size gradient distribution according to claim 1, characterized in that, The antibacterial metal nanoparticles include any one or more of silver, gold, platinum, palladium, copper, or zinc.

6. The antibacterial nanocomposite material with a particle size gradient distribution according to claim 1, characterized in that, The photocatalytic material is selected from titanium dioxide or zinc oxide, with a particle size of 100-500 nm.

7. The antibacterial nanocomposite material with a particle size gradient distribution according to claim 1, characterized in that, The interface bonding layer is a polydopamine layer with a thickness of 0.5-5 nm.

8. A method for preparing the antibacterial nanocomposite material according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Disperse the photocatalytic material in a dopamine solution and stir for 12-24 hours to form a polydopamine interface bonding layer on the outer surface of the photocatalytic material; S2. After separating and washing the product obtained in step S1, disperse it in a first aqueous solution with a concentration of 0.1-1 mM, and expose it to light with an intensity of 0.1-1 mW / cm². 2 Under ultraviolet light irradiation, the first antibacterial metal nanoparticles are deposited on the surface of the polydopamine interface layer for 5-15 minutes. S3. After separating and washing the product obtained in step S2, disperse it in a second aqueous solution with a concentration of 1-5 mM, and expose it to light with an intensity of 10-50 mW / cm². 2 Under ultraviolet light irradiation, after 30-60 minutes of deposition, a second antibacterial metal nanoparticle is formed on the surface of the polydopamine interface bonding layer.

9. The method for preparing antibacterial nanocomposite materials according to claim 8, characterized in that, The concentration of the dopamine solution is 1-5 mg / mL, the pH is adjusted to 8.0-9.0, and the reaction temperature is 20-40℃.

10. The method for preparing antibacterial nanocomposite materials according to claim 8, characterized in that, The first and second aqueous solutions also contain a hole sacrificial agent, which is selected from methanol, ethanol, isopropanol or triethanolamine.